Effects of a specific injury prevention neuromuscular training program for young female dancers. A randomized-controlled trial. Issue 2 (4th March 2023) - Cofré-Fernández, Valentina; Burgos-Estrada, Nicol; Meneses-Hermosilla, Vanessa; Ramirez-Campillo, Rodrigo; Keogh, Justin W.; Gajardo-Burgos, Rubén
ABSTRACT: To assess the effects of a specific injury prevention neuromuscular training programme (IPP) on balance and lower-limb asymmetry in female competitive dancers (age 12–20 years; height 1.57 ± 0.06 m; weight 24.27 ± 2.79 kg) were randomly allocated to an active general control (GIPP, n = 7) and specific (SIPP n = 7) group. Both programmes were conducted for 6 weeks, with a frequency of three sessions per week. Dynamic balance and lower-limb asymmetry were assessed before and after the intervention. A greater improvement in right-leg total balance (86.6[84.0–90.5] vs 93.8[86.7–99.4];p = 0.035), left-leg total balance(87.8[81.0–89.1] vs 93.6[90.6–100.0];p = 0.013), left-leg anterior balance (71.9[69.1–72.2] vs 74.6[72.0–77.3];p = 0.041), left-leg posteromedial balance (80.5[72.9–83.3] vs 85.9[83.0–94.0];p = 0.048), and left-leg posterolateral balance (79.5[70.4–84.5] vs 85.0[80.0–88.5];p = 0.048) was observed in the SIPP group compared to the GIPP group. No other significant intra-group changes nor inter-group differences were noted. Therefore, compared to a GIPP, a SIPP induced greater improvements in lower-limb dynamic balance in female dancers, potentially leading to greater reduction in lower-limb injury risk.